Voltage-Dependent Anion Channel 1 As an Emerging Drug Target for Novel Anti-Cancer Therapeutics - Shoshan-Barmatz, Varda; Krelin, Yakov; Shteinfer-Kuzmine, Anna; Arif, Tasleem (Frontiers in Oncology, 2017)
Cancer cells share a common set of properties, including unlimited proliferation potential, self-sufficiency in terms of growth signals, and resistance to anti-proliferative and apoptotic cues. Acquiring these hallmarks involves changes in key oncogenes and non-oncogenes essential for cancer cell survival and prosperity, and is accompanied by the increased energy requirements of proliferating cells. Mitochondria occupy a central position in cell life and death with mitochondrial bioenergetics, biosynthesis, and signaling are critical for tumorigenesis. Voltage-dependent anion channel 1 (VDAC1) is situated in the mitochondrial outer membrane (OMM) and serving as a mitochondrial gatekeeper. VDAC1 allowing the transfer of metabolites, ions, Ca2+, ROS and cholesterol across the OMM and is a key player in mitochondrial-mediate apoptosis. Moreover, VDAC1 serves as a hub protein, interacting with diverse sets of proteins from the cytosol, endoplasmic reticulum, and mitochondria that together regulate metabolic and signaling pathways. The observation that VDAC1 is over-expressed in many cancers suggests that the protein may play a pivotal role in cancer cell survival. However, VDAC is also important in mitochondria-mediated apoptosis, mediating release of apoptotic proteins and interacting with anti-apoptotic proteins such as Bcl-2, Bcl-xL, and hexokinase, which are also highly expressed in many cancers. Strategically located in a “bottleneck” position, controlling metabolic homeostasis and apoptosis, VDAC1 thus represents an emerging target for anti-cancer drugs. This review presents an overview on VDAC1 as a multi-functional mitochondrial protein, regulating both cell life and death, and highlights the importance of the protein for cancer cell survival. We address recent results related to the mechanisms of VDAC1-mediated apoptosis and the potential of associated proteins to modulate of VDAC1 activity, with the aim of developing VDAC1-based strategies to attack the altered metabolism and/or to activate apoptosis of cancer cells. These strategies include siRNA able to impair energy and metabolic homeostasis, leading to arrested cancer cell growth, inhibited tumor growth and reversed oncogenic properties, as well as VDAC1-based peptides that interact with anti-apoptotic proteins to induce apoptosis. Finally, we discuss the potential therapeutic benefits of treatments and drugs leading to enhanced VDAC1 expression or targeting VDAC1 to induce apoptosis.